(untitled) (SNPRC Journal, 2023)
Alternative teaching methods is a planned and organized activity which operates for alternative teaching and learning. During the COVID-19 pandemic period, the education system was highly affected and students were unable to acquire education in schools. To cope with this situation, the Nepal government released the Student Learning Facilitation Guide, 2077 to support on education system and help student getting education from home. Hence, the paper aims to examine the challenges and effectiveness of alternative teaching methods in Nepal. For this purpose, the research has been carried out with explanatory and descriptive research design. The necessary information for this study was accumulated mainly from secondary sources.